A Rare Case Report on Relapse of Takayasu’s Arteritis with Tuberculosis Relapse - Sunil Chandrasen Chand (Advanced Concepts in Medicine and Medical Research Vol. 10, 2023)
Takayasu’s Arteritis (TA) is a disease of uncertain cause with an annual incidence of 1.2 to 2.3 cases per million people. Takayasu arteritis is a rare and chronic granulomatous vasculitis that affects major elastic arteries, primarily the aorta and its main branches, as well as the pulmonary and coronary arteries, and is defined histologically by an inflammatory cell infiltrate affecting all layers of the arterial wall. Takayasu arteritis targets the aorta and its branches and is still of unknown aetiology. It often affects female patients under 50 years of age. A relationship between Takayasu arteritis and tuberculosis has been suggested for a long time. The cause of TA is unknown, but a link between TA and tuberculosis (TB) has been proposed. Mikito Takayasu, a Japanese ophthalmologist, described the first instance of Takayasu’s arteritis in 1908. Despite the link to tuberculosis and the resemblance of granulomatous lesions in both diseases, the precise involvement of Mycobacterium tuberculosis in the aetiology of TA remains uncertain.